2004
DOI: 10.4037/ajcc2004.13.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Communication Ability, Method, and Content Among Nonspeaking Nonsurviving Patients Treated With Mechanical Ventilation in the Intensive Care Unit

Abstract: • Objective To describe the communication ability, methods, and content among nonspeaking nonsurviving patients treated with mechanical ventilation in an intensive care unit.• Methods Fifty patients who received mechanical ventilation and died during hospitalization were randomly selected from all adult patients (N = 396) treated in 8 ICUs in a tertiary medical center during a 12-month period. Clinicians’ notes, use of physical restraints, and medication records were reviewed retrospectively. Data on communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 37 publications
3
50
1
2
Order By: Relevance
“…Our findings describe patients' various communication techniques and are in agreement with Happ et al (2004) study, in that the most commonly used are head nods, writing and lip-reading. Ashworth (1981) describes how patients communicated using small body movements two winks for ''no'' and one wink for ''yes''.…”
Section: Communication and Facial Expressionssupporting
confidence: 91%
“…Our findings describe patients' various communication techniques and are in agreement with Happ et al (2004) study, in that the most commonly used are head nods, writing and lip-reading. Ashworth (1981) describes how patients communicated using small body movements two winks for ''no'' and one wink for ''yes''.…”
Section: Communication and Facial Expressionssupporting
confidence: 91%
“…Communication difficulties cause distress, anger, and fear to patients and result in frustration and stress for intensive care staff (Alasad & Ahmad, 2005). Mechanically ventilated patients generally use gestures, head nods, mouthing of words, and writing to communicate with nurses (Happ, Tuite, Dobbin, Dirviglio-Thomas, & Kitutu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective descriptive study, medical records were reviewed to identify communication methods and content of communications in 50 nonspeaking, non-surviving patients who received MV in the ICU. Findings showed that communication with family caregivers often took the form of emotional expressions (Happ, Tuite, Dobbin, DiVirgilio-Thomas, & Kitutu, 2004). In a feasibility study of speech generating devices (SGDs) as an alternative communication method for MV patients (n=11), the primary content of SGD-constructed messages were "I love you" and questions about home/family (Happ, Roesch, & Garrett, 2004).…”
Section: Communication Difficulties and Family Caregiversmentioning
confidence: 99%
“…These findings suggest that VidaTalk TM allowed more complicated and emotion-laden conversations to be possible in patient-family communication during MV treatment. Previous studies also suggested that communication between family members and patients may be more stressful since the patient's conversation with the family member often took the form of emotional expressions or novel messages such as questions about home or finances (Broyles et al, 2012;Happ, Roesch, & Kagan, 2004;Happ, Tuite, et al, 2004).…”
Section: Exploration Of Participant's Experience With Vidatalk Tmmentioning
confidence: 99%